Tritium calibration of the LUX dark matter experiment - LUX collaboration (100 authors) (2016)
We present measurements of the electron-recoil (ER) response of the LUX dark matter detector based upon 170 000 highly pure and spatially uniform tritium decays. We reconstruct the tritium energy spectrum using the combined energy model and find good agreement with expectations. We report the average charge and light yields of ER events in liquid xenon at 180 and 105  V/cm and compare the results to the NEST model. We also measure the mean charge recombination fraction and its fluctuations, and we investigate the location and width of the LUX ER band. These results provide input to a reanalysis of the LUX run 3 weakly interacting massive particle search.